High-risk international clones ST66, ST171 and ST78 of Enterobacter cloacae complex causing blood stream infections in Spain and carrying blaOXA-48 with or without mcr-9 - Pilar Lumbreras-Iglesias; María de Toro; Xenia Vázquez; Enrique García-Carús; M. Rosario Rodicio; Javier Fernández (Elsevier, 2023)
Background: In the last years, Enterobacter cloacae complex has become an important threat associated with nosocomial infections (including bacteraemia). These bacteria have the ability to acquire mobile genetic elements with antimicrobial resistance genes, reducing the number of therapies available for treatment of the infections they cause. Multidrug resistant isolates of the E. cloacae complex have been causing blood stream infections in a hospital in northern Spain. The aim of this study was to report the spread of E. cloacae complex isolates carrying blaOXA-48 with or without mcr-9 which were involved in blood stream infections, in a Spanish hospital. Methods: All Enterobacter spp. isolates recovered from blood cultures of patients admitted to a tertiary Spanish hospital, over a five-year period were recovered. Of those, OXA-48-producing isolates were selected for further analysis (19 E. xiangfangensis isolates and a single E. hoffmannii). Bacterial identification, antimicrobial susceptibility, DNA sequencing, molecular typing, resistome analysis and plasmid characterization was performed. Results: 20 isolates were positive for blaOXA-48, harbored by IncL/M plasmids. They belonged to the international high-risk clones ST66, ST171 and ST78. They produced the extended-spectrum β-lactamases CTX-M-15 and/or CTX-M-9 and 40 % of them (n = 8) also carried the mcr-9 gene, located on IncHI2 plasmids. However, they were susceptible to colistin. Conclusion: The presence of blaOXA-48, together with at least one blaCTX-M gene in our multidrug resistant high-risk E. cloacae complex clones is worrisome. Also, the additional presence of mcr-9 in some of them is of concern as it could potentially be transferred into other hosts or acquire mutations that might led to emerging colistin resistance. Surveillance systems are essential to detect these difficult-to-treat bacteria which, apart from causing live-threatening infections, can spread important resistance threats.